The Effectivesness Meaning in Life and Antiretroviral Therapy (Metart) Book as an to Promotion Adherence Antiretroviral Therapy among New People Living with HIV/AIDS Asesment Pre Intervention - Yafi Sabila Rosyad1 , Firmina Theresia Kora2 , Rika Monika3 , Salis Miftahul Khoeriyah4 , I Putu Jun (Indian Journal of Forensic Medicine & Toxicology, 2020)
Adherence to ART is the primary determinant of viral suppression. Adherence of at least 95% is needed foroptimal suppression. One of relationship with HAART is meaning in life. This study aimed at assessmentmeaning in life and adherence antiretroviral therapy before intervention about METART book. This methoduse descriptive statistic analysis to explain social demographic, meaning in life, and adherence antiretroviraltherapy. The result Characteristics gender people new living with HIV/AIDS this study is 75,6% is Malewith 38,5% homosexual. The age range of respondents is in the adult (65,4%). Single merital status is74.4%. The total respondent with ARV medication is 30.8% under one year. 74.4% has meaningful life but65,4% respondent has lack adherence ARV. Conclusion this research get data pre intervention metart bookabout demographic, meaning in life, and adherence ARV.